PENGARUH KINERJA KEUANGAN, KEPEMILIKAN SAHAM DAN REPUTASI AUDITOR TERHADAP INTERNET FINANCIAL REPORTING PADA PERUSAHAAN SEKTOR KONSUMSI YANG TERDAFTAR DI BEI - Lia Ira Sahara; Maharani Maharani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to obtain empirical evidence regarding research on the Effect of Financial Performance, Share Ownership and Auditor Reputation on Internet Financial Reporting (On Consumption Sector Companies Listed on the Indonesia Stock Exchange). This study aims to determine the ability of Financial Performance, Share Ownership and Auditor Reputation to influence Internet Financial Reporting. Go public companies that apply Internet Financial Reporting (IFR) on the company's website tend to use the services of a public accountant who has a high auditor reputation with the aim of providing positive value to the company so that disclosure of information or company financial statements is disclosed through Internet Financial Reporting. This study examines the relationship between the independent variable and the dependent variable, while the method of determining the sample is purposive sampling. This type of research uses a quantitative approach, which means as a research method based on the philosophy of positivism, is used to examine certain populations or samples, collect data, use research instruments, analyze quantitative or statistical data, with the aim of testing predetermined hypotheses. The results showed that; financial performance has no effect on internet financial reporting; share ownership has an effect on internet financial reporting; auditor's report has no effect on internet financial reporting; and Financial performance, share ownership, and auditor's report together have an effect on internet financial reporting.